Martin Luther on reading the Bible as Christian scripture the Messiah in Luther's biblical hermeneutic and theology - Marsh, William M. (Eugene : Wipf and Stock Publishers, 2017)
Above all else that the sixteenth-century German Reformer was known for, Martin Luther was a Doctor of the Holy Scriptures. One of the most characteristic features of Luther's approach to Scripture was his resolved christological interpretation of the Bible. Many of the Reformer's interpreters have looked back upon Luther's ""Christ-centered"" exposition of the Scriptures with sentimentality but have often labeled it as ""Christianization,"" particularly in regards to Luther's approach of the Old Testament, dismissing his relevance for today's faithful readers of God's Word. This study revisit.
Pages:1 to 25; Pages:26 to 50; Pages:51 to 75; Pages:76 to 100; Pages:101 to 125; Pages:126 to 150; Pages:151 to 175; Pages:176 to 200; Pages:201 to 224
Description based upon print version of record.
Master record variable field(s) change: 050, 072, 082, 600, 650
Keywords: Luther, Martin, -- 1483-1546.; Jesus Christ -- History of doctrines; Hermeneutics; Messiah -- History of doctrines; RELIGION / Christian Theology / Christology; Electronic books